2013
DOI: 10.5455/ijmsph.2013.080420131
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study on substance abuse among college students of north India (Kashmir valley)

Abstract: Background: Substance abuse disorder is among the leading public health problems in modern day world as they cause enormous human suffering in terms of morbidity, mortality and economic loss; and threatens the very social fabric of almost all communities around the world and as such is a great threat to the global health, economy and peace. Like most social behaviours the etiology of substance abuse is complex, varying through time, geographical regions and by demographic characteristics. Among young people, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 8 publications
(6 reference statements)
7
29
1
1
Order By: Relevance
“…7 Current study showed age group between 20-23 years as age of initiation of substance abuse .A study by Qadri ss showed Substance abuse was more in age group of 17-19 years among school children .A study in Kashmir showed that student substance abusers were in adult age group than in adolescent group (36.2%). 8 This study showed that III year students constituted the highest percentage among substance abusers (39.4%) and final year students had prevalence of substance abuse (30.3%).A similar study by Datta et al showed 49.74% of prevalence among final year students. Alcohol was single preferred substance of use in our study (36.4%).…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…7 Current study showed age group between 20-23 years as age of initiation of substance abuse .A study by Qadri ss showed Substance abuse was more in age group of 17-19 years among school children .A study in Kashmir showed that student substance abusers were in adult age group than in adolescent group (36.2%). 8 This study showed that III year students constituted the highest percentage among substance abusers (39.4%) and final year students had prevalence of substance abuse (30.3%).A similar study by Datta et al showed 49.74% of prevalence among final year students. Alcohol was single preferred substance of use in our study (36.4%).…”
Section: Discussionmentioning
confidence: 52%
“…These newer and non-conventional substances are much more harmful and lead to greater morbidity and mortality in people abusing these drugs and especially younger generations. 8 In our Research study, the substance abuse had prevalence of 25.9% among medical students who participated in the study. It is higher than a study by Imran et al where it was found to be 17%.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations